Os espaços da modernidade: alteridades espaciais na literatura de José Lins do Rêgo (1932 - 1936) - Silva Filho, Juscelino Barros da (2021)
In this work we analyze the discursive production of the internato, the cidade and the usina, spaces of otherness in relation to the space of the engenho banguê, in the literature of the novelist and memorialist José Lins do Rêgo. We intend to problematize the symbolic dimension: meanings, values and images, mobilized by this scholar to constitute these spatialities, that is, how the figurative construction of these literary spaces takes place in his work. We start from the assumption that the most different spaces are social constructions, the result of material and symbolic investments, carried out at a given moment and by certain subjects. Our research had as main sources the works of the so-called '' sugar cane cycle '', notably the novels Doidinho (1933), Moleque Ricardo (1935) and Usina (1936), but because we are situated in the field of cultural history, we work with a variety of sources: memorial writings, newspapers and letters exchanged. Our time frame is based on the publication period of the analyzed works: it starts in 1933 - date of publication of the first novel Doidinho - and goes until 1936 - date of publication of the last one, Usina.